Power Relation in The Novel Everything, Everything by Nicola Yoon (2015) - Fadhli, Rahmat; Anwar, Desvalini (English Language and Literature, 2023)
This research is the analysis of the novel Everything, Everything by Nicola Yoon (2015). The highlight of this research is to find the discourses of power relations contained in the novel Everything, Everything by Nicola Yoon 2015, and to find the form of resistance to abuse of power in the novel Everything, Everything by Nicola Yoon 2015 and what causes it. Descriptive qualitative method is applied in this research. In this novel the researcher found that Pauline had abused her power over her daughter in 2 types of discourse. The first discourse is family, namely Pauline who has the role of a mother for her child. The second discourse is health, namely Pauline who has the role of doctor for her child. The researcher found that the daughter character (Madeline) also showed resistance in 2 different roles towards her mother, namely as a child and also as a patient.